Pengaruh Senam Aerobic Low Impact Terhadap Perubahan Tekanan Darah Pada Lansia Hipertensi di Panti Werda Damai Ranomuut Manado - Muh. Fajrin P. Luneto; I Made Rantiasa; Bayu Dwisetyo (STIKES Columbia Asia Medan, 2023)
Hypertension is a condition where there is an increase in systolic blood pressure of 140 mmHg or more and diastolic blood pressure of 90 mmHg or more. Hypertension can be caused by poor diet and lack of physical activity, The purpose of this study was to determine whether there is an influence of low impact aerobic gymnastics on changes in blood pressure in the elderly at Damai Ranomuut Nursing Home in Manado. This study was conducted with a pre post test design where the sample was observed first before being given treatment (pre test) and after being given treatment (post test) the sample was observed again. Respondents were 12 people, data collection was carried out using observation sheets. Furthermore, the data was analysed with the Wilcoxon test with a significance level (α) of 0,05. The results of the study using the T-test statistical test obtained pre-post results with a ρ value = 0,000 where the ρ value < α = 0,05. The results of this study indicate that there is an influence of low impact aerobic gymnastics on changes in blood pressure in the elderly at Damai Ranomuut Nursing Home. The conclusion of this study is that there is an influence of low impact aerobic gymnastics on changes in blood pressure in the elderly at Damai Ranomuut Nursing Home in Manado. Suggestions for the elderly at Damai Ranomuut Nursing Home to increase knowledge and awareness about the importance of maintaining health in order to avoid high blood pressure disease.